INTERNATIONAL CONFERENCE ON THE THREE PILARS OF ASEAN COMMUNITY DEVELOPMENT, 3-4 OCTOBER 2017 MERAJUT ASA DALAM : KEKERABATAN DAN KERJASAMA SOSIAL BUDAYA KHAS BANGSA-BANGSA ASEAN - B. Sulistiyono, Bambang (Feb Universitas Dirgantara Marsekal Suryadarma, 2017)
The existence of ASEAN trully did not comes apart from concerns about the South East Asian Nations which has conflicted, for example like the confrontation between Indonesia and Malaysia, territorial demand between Phillipine and Malaysia on Sabah, also the separation of Singapore from the Malaysian Federation. From those backgrounds, the South East Asian Nations especially Indonesia and Malaysia which recently conflicted, realizes the needs to form a cooperation to reduce tension, to construct confidence building and pushing regional cooperation growth which felt have no progress after each nations receive its independence. 8 August 1967 is the first ASEAN formation spearheaded by five Ministers of Foreign Affair from Indonesia, Phillipine, Malaysia, Singapore and Thailand, which resulted in the signation of ASEAN Declaration or known as The Bangkok Declaration and it also means ASEAN is formally created. One of the ASEAN's aim is